Preparation for and management during equestrian events held in thermally challenging environments - Marlin, D.; Misheff, M.; Whitehead, P. (2018)
Whilst ideally all equestrian events would be run in optimalclimatic conditions, this is often logistically not possible. Even events planned for ideal conditions can sometimes also experience unusually extreme weather. A significant amount of research has been undertaken and applied at major events since the early 1990s that has ledto improved welfare for horses through good advice, event management and improved treatment.One of the most important advances has been in understandinghow heat or heat and humidity affect horses and how to measure the level of thermal environmental stress. The FEI has adopted the Wet Bulb Globe Temperature (WBGT) Index as its method for assessing and managing thermal stress. Recognising high body temperature and the risk to horsewelfare is also essential and this document lists the signs that athletes and anyone else involved with horses at competitions should be looking for. Acclimatising horses has also been shown to help them cope better in competitions in hot or hot and humid climates, and this document explainsways of acclimatising horses. The increased demands of acclimatisation and competition in the heat may also have implications for how nutrition is managed. Travel, dehydration and changes in diet can all increase the risk of colic and care should be taken to minimise this risk.Long-distance travel is an unavoidable part of taking horses to major competitions. Studies suggest horses take a number of days to recover, particularly whenthere are changes in feed and time-zone (jet-lag) and advice is provided on best-practice to minimise health issues.In order to keep horses healthy and performing well under conditions of increasedthermal stress, some changes to normal management are indicated and these are outlined in this document. Having all team members familiar with cold-water cooling is critical to maintaining performance in the heat and reducing the risk of heat-related illness. This applies to ALL disciplines. Practising cooling procedures and ensuring everyone understandsthe need for aggressive cooling at home prior to travel is important. Athletes and support staff can also be at an increased risk of heat illness. Dehydration and high body temperature can lead to weakness,disorientation and poor decision making. Therefore,it is vital that athletes and other team members take extra care in challenging conditions and are aware of how to decrease the risk of heat related illness and recognise and know how to manage it.Finally, recognising that a horse is not coping with the heat and seeking veterinary help can ensure that horsec an remain in competition and avoid significant injury. An outline of how to recognise and manage horsessuffering from heat exhaustion or heat stroke is also provided